Triboluminescence and triboelectricity: toward next-generation wearable light sources - See, Zhi Qiang (Nanyang Technological University, 2023)
The use of triboelectric nanogenerators (TENGs) in the field of intelligent motion is becoming more common due to their outstanding performance and great output characteristics, and research and development are progressing at a rapid pace. This research paper provides a comprehensive overview of the utilisation of triboelectric nanogenerators (TENG) to create an x-ray source using waste/green material that can be commonly seen in our daily lives. The paper comprises four main sections: underlying mechanisms and fundamentals of physics, advances in triboluminescence, literature review of the waste triboelectric generator (W-TENG) with experiments using commonly seen items, and factors affecting the output. This work presents the idea of using waste or commonly seen items as materials to generate X-rays.